The Effectiveness of Attachment-Based Cognitive Integrative Therapy on Early Maladaptive Schemas, Dysfunctional Beliefs, and Depression - Motejadded, Somayeh; Karimzadeh, Fatemeh; Soltani Razavi, Shima (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of attachment-based cognitive integrative therapy on early maladaptive schemas, dysfunctional beliefs, and depressive symptoms in individuals with depression. Methods and Materials: This study employed a quasi-experimental design with pre-test, post-test, and two-month follow-up, including an experimental group and a control group. The statistical population consisted of individuals with depressive symptoms who referred to psychological counseling centers in Tehran. A total of 40 participants were selected through purposive sampling and randomly assigned into two groups of 20 (experimental and control). The experimental group received 12 sessions of attachment-based cognitive integrative therapy, while the control group remained on a waiting list. Data were collected using the Young Schema Questionnaire–Short Form (YSQ-SF), Dysfunctional Attitude Scale (DAS), and Beck Depression Inventory-II (BDI-II). Data analysis was conducted using repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc tests in SPSS-27. Findings: The results of repeated measures ANOVA indicated significant effects of time, group, and the interaction between time and group on early maladaptive schemas, dysfunctional beliefs, and depression (p < 0.001). The experimental group showed significant reductions in all three variables compared to the control group, with large effect sizes observed across outcomes. Bonferroni post-hoc tests revealed that the differences between pre-test and post-test, as well as pre-test and follow-up, were statistically significant (p < 0.001), while no significant differences were found between post-test and follow-up, indicating the stability of treatment effects over time. Conclusion: Attachment-based cognitive integrative therapy is an effective intervention for reducing early maladaptive schemas, dysfunctional beliefs, and depressive symptoms, with sustained effects over time, suggesting its potential as a comprehensive therapeutic approach targeting both cognitive and relational dimensions of depression.